An investigation into the origins and manifestation of piracy in the Zimbabwean film industry - Dikito, Vincent Tinotenda (Midlands State University, 2017)
The Zimbabwean film industry is a troubled industry and one of the factors hindering its growth and development is piracy. The proliferation of this practice has resulted in the underdevelopment of the industry to the extent that some critics now believe that there is no film industry. This study critically investigates the origins and manifestation of piracy in the Zimbabwean film industry. Most people have a shallow understanding of the term piracy and they have little knowledge of its forms. As a result, a number of people practise and promote piracy without knowing it. The study discusses a number of forms in which piracy manifests itself in in the Zimbabwean context as well as its history. Factors exacerbating this anomaly were analysed and probable solutions to the problem were presented.